Early Modern Discussions about Ancient China - Lejiamei Chen (Asian Studies)
Early modern discussions about ancient China have largely been studied from the perspective of how images of ancient China were portrayed in missionary narratives. This article, however, attempts to investigate how interactions between China and Europe have contributed to the evolution of historical studies in early modern Europe. By analysing different studies by Jesuit authors and European savants about ancient China, this article first traces how ancient Chinese history provides a new alternative to the origin stories of humankind, undermining the dominant biblical approach to history. While defending the old origin story, missionaries changed their narratives about ancient China. Further investigation into the historical sources used by Jesuit authors shows the application of different materials across the two centuries, and these changes in materials also create a polyphony in their written accounts. By introducing various historical sources and textual traditions to Europe, missionaries, who served as intercultural agents, participated actively in the multiplication of primary sources for European historical research. The changing historical methodologies in the studies about ancient China are also examined, particularly how the transition from astronomical to linguistic methods occurred during the eighteenth century, reshaping the discourse on ancient China. This article tackles the important question of how intercultural exchanges about ancient Chinese history participated in the transformation of historical studies from a chronological study to modern historiography.